Unified cyclic stress–strain model for normal and high strength concrete confined with FRP. (1st November 2015) - Yu, T.; Zhang, B.; Teng, J.G.
Highlights: A unified cyclic stress–strain model for normal and high strength concrete confined with FRP is presented. The proposed model is an extension of Lam and Teng cyclic stress–strain model. The proposed model is based on a large test database and deals thoroughly with the effect of concrete strength. The proposed model provides accurate predictions of experimental results. Abstract: Fiber reinforced polymer (FRP) has become increasingly popular as a confining material for concrete, both in the strengthening of existing columns where FRP wraps with fibers oriented completely or predominantly in the hoop direction are typically used, and in new construction where filament-wound FRP tubes with fibers oriented at desired angles to the longitudinal axis are typically used. For both types of applications, the stress–strain behavior of FRP-confined concrete under cyclic axial compression needs to be properly understood and modeled for the accurate simulation of such columns under seismic loading. This paper presents an improved cyclic stress–strain model for FRP-confined concrete on the basis of a critical assessment of an earlier model proposed by Lam and Teng in 2009 by making use of a database containing new test results of both concrete-filled FRP tubes (CFFTs) and concrete cylinders confined with an FRP wrap. The assessment reveals several deficiencies of Lam and Teng's model due to the limited test results available to them. The proposed model corrects these deficiencies and is shown to provide reasonably accurate predictions for both concrete in CFFTs and concrete confined with an FRP wrap and for both normal strength concrete (NSC) and high strength concrete (HSC).